Development of a Complex Orientation Program for Multidisciplinary Training. - Hemingway, Maureen; Morrissey, Lisa (AORN Journal, 2013)
Providing complex orientation and multidisciplinary training for perioperative personnel of a newly constructed health care facility with new surgical suites proved both challenging and valuable to nurse leaders. Despite the need for such training, a program to teach groups across all disciplines regarding technological advances specific to the OR and to orient them to a new facility did not exist previously. To address this, we developed a multiphase educational initiative that involved orientation, technology training, and multidisciplinary simulation. The project required extensive planning, high-level collaboration, and use of the hospital's information technology systems, all while staff members continued to provide care for patients undergoing surgically complex procedures. The successful implementation of this program ensured that staff members were proficient in new OR technology and oriented to the new facility before occupancy began. AORN J 97 (June 2013) 718-727.AORN, Inc, 2013.